Glass article, method of producing glass article, and display device
By adjusting the concentration ratio of hydrogen ions and alkali ions at a depth of 30 nm on the surface of the glass product, and combining LAS glass ceramics and chemical reinforcement technology, the problem of insufficient strength of glass products under external impact is solved, achieving both high impact resistance and thin thickness.
Patent Information
- Application Number
- CN202411449020.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing glass products are insufficient in the face of external impact, especially in portable electronic devices, and thin glass products are difficult to take into account both small thickness and high strength.
By adjusting the concentration ratio of hydrogen ions and alkali ions at a depth of 30 nm on the surface of the glass product, so that it is equal to or greater than 1:4, combined with LAS glass ceramics and a specific chemical reinforcement process, the impact resistance of the glass product is improved.
The impact resistance of glass products is significantly improved, allowing them to resist external impact more effectively while maintaining thin properties for easy folding and use.
Smart Images

Figure CN119841560A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate to glass products, methods of producing glass products, and display devices. Background Art
[0002] Glass products are widely used in electronic devices including display devices and / or building materials. For example, glass products are used as substrates for flat panel display devices such as liquid crystal display (LCD) devices, organic light emitting display (OLED) devices, and electrophoretic display (EPD) devices, and / or windows for protecting them.
[0003] As portable electronic devices such as smart phones and tablet personal computers become ubiquitous, glass products used therein are often exposed to external impacts. There is a need for the development of thin glass products that are easy to transport and can withstand external impacts.
[0004] Recently, foldable display devices have been studied for the convenience of users. Glass products applied to foldable display devices should have a small thickness to relieve bending stress when folded, and have strength capable of withstanding external impact. Therefore, attempts have been made to improve the strength of thin glass products by changing the production process conditions of glass products. Summary of the invention
[0005] Aspects of embodiments of the present disclosure provide a glass product capable of improving impact resistance, a method of producing the glass product, and a display device.
[0006] It should be noted that the objects of the embodiments of the present disclosure are not limited to the above objects, and other objects of the embodiments of the present disclosure will be apparent to those skilled in the art through the following description.
[0007] According to aspects of an embodiment of the present disclosure, a glass article is provided, wherein the ratio of the intensity (e.g., concentration) of hydrogen ions at a depth of 30 nm from the surface of the glass article to the intensity (e.g., concentration) of hydrogen ions at the surface is equal to or greater than 1:4.
[0008] In an embodiment, a ratio of the intensity (eg, concentration) of hydrogen ions at a depth of 30 nm from the surface to the intensity (eg, concentration) of hydrogen ions at the surface ranges from 1:4 to 1:6.
[0009] In an embodiment, the ratio of the intensity (eg, concentration) of alkali ions at a depth of 30 nm from the surface to the intensity (eg, concentration) of alkali ions at the surface ranges from 1:0.05 to 1:0.1.
[0010] In an embodiment, the glass article comprises a LAS glass-ceramic.
[0011] In an embodiment, the glass article comprises SiO 2 , Li 2 O and Al 2 O 3 , and also includes selected from Na 2 O.K 2 O, MgO, P 2 O 5 , B 2 O 3 ,CaO, SrO, BaO, ZnO, TiO 2 and ZrO 2 At least one of .
[0012] In an embodiment, the glass article has a thickness ranging from 20 μm to 100 μm.
[0013] In an embodiment, the glazing is foldable.
[0014] According to aspects of an embodiment of the present disclosure, a method for producing a glass product is provided, which includes forming glass, stacking glass to construct a glass stack, cutting the glass stack to separate it into individual glasses, performing a first repair on the glass, performing a first cleaning on the glass, strengthening the glass, performing a second cleaning on the glass, performing a second repair on the glass, and performing a third cleaning on the glass, wherein at least one of the first cleaning, the second cleaning, and the third cleaning uses deionized water at a temperature in the range of 80°C to 100°C.
[0015] In an embodiment, at least one selected from the first cleaning, the second cleaning, and the third cleaning is performed by dipping or spraying.
[0016] In an embodiment, at least one selected from the first cleaning, the second cleaning, and the third cleaning is performed for several minutes to several tens of minutes.
[0017] In an embodiment, in at least one selected from the first cleaning, the second cleaning, and the third cleaning, hydrogen ions and alkali ions are ion-exchanged at the surface of the glass.
[0018] In an embodiment, the method further comprises performing a fourth cleaning of the glass between the separating and the first repairing, wherein the fourth cleaning uses deionized water at a temperature in a range of 80°C to 100°C.
[0019] In an embodiment, the method further includes chamfering the glass after cutting the glass stack, wherein the chamfering is performed by a chemical polishing process.
[0020] According to aspects of an embodiment of the present disclosure, a display device is provided, comprising a display panel including a plurality of pixels, a cover window on the display panel, and an optically transparent connecting layer between the display panel and the cover window, wherein a ratio of an intensity (e.g., a concentration) of hydrogen ions at a depth of 30 nm from a surface of the cover window to an intensity (e.g., a concentration) of hydrogen ions at the surface is equal to or greater than 1:4.
[0021] In an embodiment, in the cover window, a ratio of the intensity (eg, concentration) of hydrogen ions at a depth of 30 nm from the surface to the intensity (eg, concentration) of hydrogen ions at the surface ranges from 1:4 to 1:6.
[0022] In an embodiment, in the cover window, a ratio of the intensity (eg, concentration) of alkali ions at a depth of 30 nm from the surface to the intensity (eg, concentration) of alkali ions at the surface ranges from 1:0.05 to 1:0.1.
[0023] In an embodiment, the cover window comprises LAS glass-ceramic.
[0024] In an embodiment, the cover window comprises SiO 2 , Li 2 O and Al 2 O 3 , and also includes selected from Na 2 O.K 2 O, MgO, P 2 O 5 , B 2 O 3 ,CaO, SrO, BaO, ZnO, TiO 2 and ZrO 2 At least one of .
[0025] In an embodiment, the cover window has a thickness ranging from 20 μm to 100 μm.
[0026] In an embodiment, the cover window is foldable.
[0027] According to an embodiment of the present disclosure, during the process of cleaning a glass article, the strength (e.g., concentration) of hydrogen ions on the surface of the glass can be increased while the strength (e.g., concentration) of alkali ions can be reduced, thereby improving the impact resistance of the glass article.
[0028] It should be noted that the effects of the embodiments of the present disclosure are not limited to the above-mentioned effects, and other effects of the embodiments of the present disclosure will be apparent to those skilled in the art through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and other aspects and features of embodiments of the present disclosure will become more apparent by describing the embodiments of the present disclosure in more detail with reference to the accompanying drawings.
[0030] Figure 1 is a perspective view of a glass article according to various embodiments.
[0031] Figure 2 is a perspective view showing a display device employing a glass article according to an embodiment of the present disclosure when unfolded.
[0032] Figure 3 It is shown Figure 2 A perspective view of the display device when folded.
[0033] Figure 4 is a cross-sectional view showing an example in which the glass article according to an embodiment of the present disclosure is employed as a cover window of a display device.
[0034] Figure 5 is a cross-sectional view of a glass article having a flat plate shape according to an embodiment of the present disclosure.
[0035] Figure 6 is a graph showing stress distribution of a glass article according to an embodiment of the present disclosure.
[0036] Figure 7 is a flow chart illustrating a method of producing a glass article according to an embodiment of the present disclosure.
[0037] Figure 8 is a view illustrating a cleaning process according to an embodiment.
[0038] Fig. 9 is a view illustrating ion exchange in a cleaning process according to an embodiment.
[0039] Fig.10 is a view showing ion exchange in a strengthening process according to an embodiment.
[0040] Fig.11 is a graph showing the results of a pen pressure test of glasses according to Examples and Comparative Examples.
[0041] Fig.12 is a graph showing the results of a pen drop test on glasses according to Examples and Comparative Examples.
[0042] Fig.13 is a graph showing the distribution of hydrogen ions in glass products measured according to Examples and Comparative Examples.
[0043] Fig.14 is a graph showing the distribution of alkali ions in glass products measured according to Examples and Comparative Examples. DETAILED DESCRIPTION
[0044] The subject matter of the present disclosure will now be described more fully below with reference to the accompanying drawings in which preferred embodiments of the present disclosure are shown. However, the subject matter of the present disclosure can be implemented in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present disclosure to those skilled in the art.
[0045] It will also be understood that when a layer is referred to as being 'on' another layer or substrate, it can be directly on the other layer or substrate, or intervening layers may also be present. Like reference numerals refer to like components throughout the specification.
[0046] It should be understood that although the terms "first", "second", etc. may be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the spirit or scope of the present disclosure, the first element discussed below may be referred to as the second element. Similarly, the second element may also be referred to as the first element.
[0047] Each of the features of the various embodiments of the present disclosure can be combined in part or in whole or in combination with each other, and various suitable interlocks and drives are technically possible. Each embodiment can be implemented independently of each other, or can be implemented together in association.
[0048] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings.
[0049] Figure 1 is a perspective view of a glass article according to various embodiments.
[0050] Glass can be used as a cover window for protecting a display, a substrate for a display panel, a substrate for a touch panel, an optical member such as a light guide plate, etc. in an electronic device including a display (such as a tablet personal computer, a notebook personal computer, a smart phone, an e-book, a television, and / or a personal computer monitor) and a refrigerator and / or a washing machine including a display. Glass can also be used as a cover glass for an instrument panel in a vehicle, a cover glass for a solar cell, an interior material for a building material, a window for a building and / or a house, etc.
[0051] Glass should have high strength. For example, when glass is used as a window, it is desirable to have a small thickness and high strength so that it is not easily broken by external impact because it should have high transmittance and low weight. Glass with high strength can be produced by, for example, chemical strengthening and / or thermal tempering. Figure 1 Examples of tempered glass in various shapes are shown in FIG.
[0052] Reference Figure 1 In an embodiment, the glass article 100 may have a flat sheet or plate shape. In another embodiment, the glass articles 101, 102, and 103 may each have a three-dimensional shape including a curved portion. For example, the edge of the flat portion may be bent (e.g., glass article 101), the entire surface may be bent (e.g., glass article 102) and / or folded (e.g., glass article 103). In some embodiments, the glass article 100 may be a foldable glass article, which has a flat sheet or plate shape and is flexible so that it can be folded and / or bent. In some embodiments, the glass article 100 can be stretched and / or curled. The glass articles 100, 101, 102, and 103 may each have a first surface US, a second surface RS, and a side surface SS.
[0053] When viewed from the top, the shape of the glass articles 100 to 103 may be, but is not limited to, a rectangle. For example, the glass articles 100 to 103 may have various suitable shapes, such as a rounded rectangle, a square, a circle, and / or an oval. In the following description, a glass article having a rectangular flat plate shape will be described as an example of the glass articles 100 to 103. However, it should be understood that the present disclosure is not limited thereto.
[0054] Figure 2 is a perspective view showing a display device employing a glass article according to an embodiment of the present disclosure when unfolded. Figure 3 It is shown Figure 2 A perspective view of the display device when folded.
[0055] Reference Figure 2 and Figure 3 According to the embodiment, the display device 500 may be a foldable display device. As will be further described below, the display device 500 may be a foldable display device. Figure 1 The glass article 100 serves as a cover window, and the glass article 100 may be flexible and foldable.
[0056] like Figure 2 and Figure 3 As shown in , the first direction DR1 may refer to a direction parallel to one side of the display device 500, for example, a horizontal direction of the display device 500 when viewed from the top. The second direction DR2 may refer to a direction parallel to the other side of the display device 500 intersecting the one side of the display device 500, for example, a vertical direction of the display device 500 when viewed from the top. The third direction DR3 may refer to a thickness direction of the display device 500.
[0057] According to an embodiment of the present disclosure, the display device 500 may have a rectangular shape when viewed from the top. When viewed from the top, the display device 500 may have a rectangular shape with sharp corners or a rectangular shape with rounded corners. When viewed from the top, the display device 500 may include two short sides extending in the first direction DR1 and two long sides extending in the second direction DR2.
[0058] The display device 500 includes a display area DA and a non-display area NDA. When viewed from the top, the shape of the display area DA may conform to the shape of the display device 500. For example, when the display device 500 is rectangular when viewed from the top, the display area DA may also be rectangular.
[0059] The display area DA may include a plurality of pixels to display an image. The plurality of pixels may be provided in a matrix pattern. When viewed from the top, the plurality of pixels may be, but are not limited to, a rectangle, a rhombus, or a square. For example, when viewed from the top, the plurality of pixels may be a quadrilateral other than a rectangle (e.g., a rhombus), a polygon other than a quadrilateral, a circle, or an ellipse.
[0060] The non-display area NDA may not include pixels and thus may not display an image. The non-display area NDA may be provided around the display area DA. The non-display area NDA may surround the display area DA, but the present disclosure is not limited thereto. The display area DA may be partially surrounded by the non-display area NDA.
[0061] According to an embodiment, the display device 500 can remain folded and unfolded. Figure 3 As shown in , the display device 500 may be folded inward (folded inward) so that the display area DA is positioned inside. When the display device 500 is folded inward (folded inward), a portion of the upper surface of the display device 500 may face another portion thereof. As another example, the display device 500 may be folded outward (folded outward) so that the display area DA is positioned outside. When the display device 500 is folded outward (folded outward), a portion of the lower surface of the display device 500 may face another portion thereof.
[0062] According to an embodiment of the present disclosure, the display device 500 may be a foldable display device. As used herein, a foldable display device refers to a display device that can be folded and can be switched between a folded state and an unfolded state. When the device is folded, the device is usually folded at an angle of approximately 180°. However, it should be understood that the present disclosure is not limited thereto. For example, when the device is folded at an angle greater than or less than 180° (e.g., at an angle of 90° or greater and less than 180° or an angle of 120° or greater and less than 180°), the device is also referred to as folded. In some embodiments, even when the device is not completely folded, if the device is not unfolded but slightly bent, the device may also be referred to as folded. For example, even if the device is bent at an angle of 90 degrees or less, as long as the maximum folding angle is 90 degrees or more, the device may also be referred to as folded to distinguish it from unfolding. When the display device is folded, the radius of curvature may be 5 mm or less, for example, in the range of 1 mm to 2 mm, or may be approximately 1.5 mm. It should be understood that the present disclosure is not limited thereto.
[0063] According to an embodiment of the present disclosure, the display device 500 may include a folding area FDA, a first non-folding area NFA1, and a second non-folding area NFA2. The display device 500 can be folded at the folding area FDA, but cannot be folded at the first non-folding area NFA1 and the second non-folding area NFA2.
[0064] The first non-folding area NFA1 may be located on one side (eg, upper side) of the folding area FDA. The second non-folding area NFA2 may be located on the other side (eg, lower side) of the folding area FDA. The folding area FDA may be a bending area having a set predetermined curvature.
[0065] According to an embodiment, the folding area FDA may be positioned at a set or specific position in the display device 500. In the display device 500, one or more folding areas FDA may be positioned at a set or specific position. According to another embodiment, the position of the folding area FDA may not be limited in the display device 500, but may be freely formed in different areas.
[0066] According to an embodiment, the display device 500 may be foldable in the second direction DR2. Therefore, the length of the display device 500 in the second direction DR2 may be reduced to about half, making the display device 500 convenient to carry.
[0067] According to an embodiment of the present disclosure, the folding direction of the display device 500 is not limited to the second direction DR2. For example, the display device 500 may be folded in the first direction DR1. In some embodiments, the length of the display device 500 in the first direction DR1 may be reduced to about half.
[0068] In the drawings, each of the display area DA and the non-display area NDA overlaps with the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2. However, it should be understood that the present disclosure is not limited thereto. For example, each of the display area DA and the non-display area NDA may overlap with at least one of the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2.
[0069] Figure 4 is a cross-sectional view showing an example in which the glass article according to an embodiment of the present disclosure is employed as a cover window of a display device.
[0070] Reference Figure 4 , the display device 500 may include a display panel 200, a glass article 100 located on the display panel 200 and serving as a cover window, and an optically transparent coupling layer 300 located between the display panel 200 and the glass article 100 to couple them.
[0071] For example, the display panel 200 may include a self-luminous display panel such as an organic light emitting display panel (OLED), an inorganic light emitting display panel (inorganic EL), a quantum dot light emitting display panel (QED), a micro LED display panel (micro LED), a nano LED display panel (nano LED), a plasma display panel (PDP), a field emission display panel (FED) and / or a cathode ray display panel (CRT), and a light receiving display panel such as a liquid crystal display panel (LCD) and / or an electrophoretic display panel (EPD).
[0072] The display panel 200 may include a plurality of pixels PX, and may display an image by using light emitted from each of the plurality of pixels PX. The display device 500 may further include a touch member. According to an embodiment of the present disclosure, the touch member may be incorporated into the display panel 200. For example, the touch member may be directly formed on the display member of the display panel 200, and thus the display panel 200 itself may perform or provide a touch feature. According to another embodiment, the touch member may be manufactured separately from the display panel 200, and then attached to the upper surface of the display panel 200 through an optically transparent coupling layer.
[0073] The glass article 100 protecting the display panel 200 is located above the display panel 200. The glass article 100 may be larger than the display panel 200 so that its side surface may protrude outward from the side surface of the display panel 200. However, it should be understood that the present disclosure is not limited thereto. The display device 500 may further include a printed layer on at least one surface of the glass article 100 at an edge of the glass article 100. In some embodiments, the printed layer of the display device 500 may hide the frame of the display device 500 from the outside and may provide decoration.
[0074] The optically transparent coupling layer 300 is located between the display panel 200 and the glass article 100. The optically transparent coupling layer 300 is used to fix the glass article 100 on the display panel 200. The optically transparent coupling layer 300 may include an optically clear adhesive (OCA), an optically clear resin (OCR), and the like.
[0075] Hereinafter, the tempered glass article 100 will be described in more detail.
[0076] Figure 5 is a cross-sectional view of a glass article having a flat plate shape according to an embodiment of the present disclosure.
[0077] Reference Figure 5 , the glass article 100 may include a first surface US, a second surface RS, and a side surface. In the glass article 100 having a flat plate shape, the first surface US and the second surface RS are main surfaces having a large area, and the side surface SS ( Figure 1 ) is an outer surface connecting the first surface US and the second surface RS.
[0078] The first surface US and the second surface RS are opposite to each other in the thickness direction (e.g., facing away from each other). When the glass article 100 is used to transmit light like a cover window of a display, light may be mainly incident on one of the first surface US and the second surface RS to be emitted through the other of the first surface US and the second surface RS.
[0079] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may be, but is not limited to, 100 μm or less, or, for example, may be in the range of 20 μm to 100 μm. According to an embodiment of the present disclosure, the thickness t of the glass article 100 may be 80 μm or less. According to another embodiment, the thickness t of the glass article 100 may be approximately 75 μm or less. According to yet another embodiment, the thickness t of the glass article 100 may be approximately 70 μm or less. According to yet another embodiment, the thickness t of the glass article 100 may be approximately 60 μm or less. According to yet another embodiment, the thickness t of the glass article 100 may be approximately 65 μm or less. According to yet another embodiment, the thickness t of the glass article 100 may be approximately 50 μm or less. According to yet another embodiment, the thickness t of the glass article 100 may be approximately 30 μm or less. In some embodiments, the glass article 100 may have a thickness t in the range of 20 μm to 50 μm, or approximately 30 μm. The glass article 100 may have a uniform thickness t, or may have different thicknesses for different regions (eg, may have a non-uniform thickness t).
[0080] The glass article 100 may be tempered to have a set or predetermined stress distribution therein. Compared with the glass article 100 before tempering, the tempered glass article 100 can better prevent or reduce the occurrence and / or propagation of cracks, breakage caused by external impact, etc. The glass article 100 tempered by the tempering process may have different stresses according to its different zones. For example, the compression zones CSR1 and CSR2 with compressive stress may be located near the surface of the glass article 100, for example, near the first surface US and the second surface RS, and the tensile zone CTR with tensile stress may be located inside the glass article 100 (hereinafter, for the convenience of explanation, the compression zone CSRn and the nth compression zone CSRn indicate the same features and are not particularly distinguished in the description). The boundary between the tensile zone CTR and each of the compression zones CSR1 and CSR2 may have a stress value of zero. The value of the compressive stress in each of the compression zones CSR1 and CSR2 may change according to the position (for example, the depth from the surface). In some embodiments, the tensile region CTR may also have different stress values according to the depths from the first surface US and the second surface RS.
[0081] The positions of the compression regions CSR1 and CSR2 in the glass article 100 , the stress distribution in the compression regions CSR1 and CSR2 , the compression energy of the compression regions CSR1 and CSR2 , the tension energy of the tension region CTR, etc. may greatly affect the mechanical properties of the glass article 100 , such as surface strength.
[0082] Figure 6 is a graph showing stress distribution of a glass article according to an embodiment of the present disclosure. Figure 6 In the graph of , the x-axis represents the thickness direction of the glass article, which is hereinafter referred to as "thickness t direction". Figure 6 In the present invention, compressive stress has a positive value, while tensile stress has a negative value. In this paper, the magnitude of compressive / tensile stress means the absolute value regardless of its sign.
[0083] Reference Figure 6 , the glass article 100 includes a first compression zone CSR1 extending (or extending) from the first surface US to a first compression depth DOC1 and a second compression zone CSR2 extending (or extending) from the second surface RS to a second compression depth DOC2 (hereinafter, for the convenience of explanation, the compression depth DOCn and the nth compression depth DOCn indicate the same feature and are not particularly distinguished in the description). The tensile zone CTR is located between the first compression depth DOC1 and the second compression depth DOC2. The stress distribution on the first surface US and the stress distribution on the second surface RS of the glass article 100 may be symmetrical with respect to the center of the thickness t direction. In some embodiments, the compression zone and the tensile zone may be formed between opposite side surfaces of the glass article 100 in a similar manner.
[0084] The first compression region CSR1 and the second compression region CSR2 resist external impact to prevent or reduce the occurrence of cracks in the glass article 100 and / or damage to the glass article 100. The greater the maximum compressive stress CS1 of the first compression region CSR1 and the maximum compressive stress CS2 of the second compression region CSR2, the higher the strength of the glass article 100. Since external impact is generally transmitted through the surface of the glass article 100, it is beneficial or advantageous in terms of durability to have the maximum compressive stresses CS1 and CS2 at the surface of the glass article 100. In view of the above, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 are the largest at the surface and generally decrease toward the inside.
[0085] The first compression depth DOC1 and the second compression depth DOC2 inhibit or reduce the propagation of cracks and / or grooves formed in the first surface US and the second surface RS to the tensile region CTR inside the glass article 100. The larger the first compression depth DOC1 and the second compression depth DOC2, the more the propagation of cracks and / or the like can be prevented or reduced. The positions of the first compression depth DOC1 and the second compression depth DOC2 are the boundaries between the tensile region CTR and each of the compression regions CSR1 and CSR2, and the stress value is zero at the boundaries.
[0086] In the entire glass article 100, the tensile stress of the tensile region CTR may be balanced with the compressive stress of the compressive regions CSR1 and CSR2. In some embodiments, in the glass article 100, the sum of the compressive stresses (e.g., compressive energy) may be equal to the sum of the tensile stresses (e.g., tensile energy). The stress energy accumulated in a region having a constant width in the thickness t direction in the glass article 100 may be calculated by integrating the stress distribution. When the stress distribution in the glass article 100 having a thickness of t is represented by the function f(x), the following relationship can be established:
[0087] Equation 1
[0088]
[0089] The greater the tensile stress inside the glass article 100, the more likely the fragments will be violently released when the glass article 100 breaks, and the more likely the glass article 100 will be crushed from the inside. For example, the maximum tensile stress that satisfies the brittleness requirement of the glass article 100 may satisfy the following relationship:
[0090] Equation 2
[0091] CT 1 ≤-38.7×ln(t)+48.2
[0092] In some embodiments, the maximum tensile stress CT1 may be 100 MPa or less, or 85 MPa or less. In order to improve mechanical properties such as strength, it is desirable that the maximum tensile stress CT1 is 75 MPa or more. According to an embodiment of the present disclosure, the maximum tensile stress CT1 may be, but is not limited to, 75 MPa or more and 85 MPa or less.
[0093] The maximum tensile stress CT1 of the glass article 100 may generally be located at a central portion of the glass article 100 in the thickness t direction. For example, the maximum tensile stress CT1 of the glass article 100 may be located at a depth in a range of 0.4t to 0.6t, at a depth in a range of 0.45t to 0.55t, or at a depth of approximately 0.5t.
[0094] Although it is desirable that the compressive stress and the compression depths DOC1 and DOC2 have large values to improve the strength of the glass article 100, the tensile stress may also increase when the tensile energy increases with the compression energy. In order to meet the brittleness requirement while having high strength, it may be desirable to adjust the stress distribution so that the maximum compressive stresses CS1 and CS2 and the compression depths DOC1 and DOC2 have large values while the compression energy is reduced. To this end, the glass article 100 may be produced by a glass composition containing certain components of a set or predetermined content (e.g., amount). According to the component ratio of the components contained in the glass composition, the glass article 100 can have excellent strength, as well as flexibility and properties, so that it can be applied to a foldable display device.
[0095] Hereinafter, a method of producing a glass product will be described. In the following description, the same or similar elements will be denoted by the same or similar reference numerals, and redundant descriptions will be omitted or briefly described.
[0096] Figure 7 is a flow chart illustrating a method of producing a glass article according to an embodiment of the present disclosure. Figure 8 is a view illustrating a cleaning process according to an embodiment. Fig. 9 is a view illustrating ion exchange in a cleaning process according to an embodiment. Fig.10 is a view showing ion exchange in a strengthening process according to an embodiment.
[0097] Reference Figures 7 to 10 , the method for producing a glass product according to an embodiment may include forming (S10), first cleaning (S20), stacking (S30), cutting (S40), chamfering (S50), separating (S60), second cleaning (S70), first repairing (S80), third cleaning (S90), strengthening (S100), fourth cleaning (S110), second repairing (S120) and fifth cleaning (S130).
[0098] The forming S10 may include preparing a glass composition and forming the glass composition.
[0099] The glass composition may include various suitable components commonly used in the art. According to an embodiment of the present disclosure, the glass composition may include LAS glass ceramics including lithium aluminosilicates. For example, the glass composition may include 50 mol % to 80 mol % of SiO 2 , 1 mol% to 30 mol% Al 2 O 3 , 0 mol% to 5 mol% B 2 O 3 , 0 mol% to 4 mol% P 2 O 5 , 3 mol% to 20 mol% Li 2 O, 0 mol% to 20 mol% Na 2 O, 0 mol% to 10 mol% K 2 O, 3 mol% to 20 mol% MgO, 0 mol% to 20 mol% CaO, 0 mol% to 20 mol% SrO, 0 mol% to 15 mol% BaO, 0 mol% to 10 mol% ZnO, 0 mol% to 1 mol% TiO 2 and / or 0 mol% to 8 mol% ZrO 2 However, it should be understood that the present disclosure is not limited thereto. The glass composition may include SiO 2 、Al 2 O 3 and Li 2 O, and may also include a selection from B 2 O 3 , P 2 O 5 、Na 2 O.K 2 O, MgO, CaO, SrO, BaO, ZnO, TiO 2 and ZrO 2 One or more of .
[0100] As used herein, a content of 0 mol% of an ingredient means that the ingredient is substantially not included. As used herein, the phrase "the composition does not substantially include a specific ingredient" means that the ingredient is not intended to be included in raw materials and / or the like, and may inevitably contain a small amount of impurities of 0.1 mol% or less.
[0101] The components of the glass composition will be described in more detail. The glass includes SiO 2 Or mainly composed of SiO2 Composition, SiO 2 It can improve chemical durability and can inhibit or reduce the occurrence of cracks when scratches (dents) are formed on the surface of the glass. In order to fully achieve the above effects, SiO 2 The content may be 50 mol% or more. In order to exhibit sufficient fusibility, the SiO in the glass composition 2 The content may be 80 mol% or less.
[0102] Al 2 O 3 Provides better properties for the glass when it breaks. In other words, when the glass breaks, Al 2 O 3 The amount of fragments formed can be reduced. In some embodiments, Al 2 O 3 It can be used as an effective component to improve ion exchange during the chemical strengthening process and increase surface compressive stress after strengthening. 2 O 3 When the content of Al is 1 mol% or more, the above effects can be effectively achieved. In some embodiments, in order to maintain the acid resistance and melting property of the glass, it is desirable to make Al 2 O 3 The content is 30 mol% or less.
[0103] B 2 O 3 Improves the chipping resistance of the glass and improves the melting property. Although B can be eliminated or omitted 2 O 3 (0 mol%), but the melting property of the glass is improved when it contains 0.5 mol% or more of B 2 O 3 When B 2 O 3 When the content is 5 mol% or less, cords can be advantageously suppressed or reduced during a melting process.
[0104] P 2 O 5 Improve ion exchange performance and crack resistance. Although P 2 O 5 (0 mol%), but the above functions are contained in 0.5 mol% or more of P 2 O 5 When P 2 O 5 When the content is equal to or less than 4 mol%, it may be advantageous or beneficial to prevent or reduce the significant reduction in brittleness and acid resistance.
[0105] Li 2 O forms surface compressive stress through ion exchange. Li ions near the glass surface can be exchanged by Na ions and the like through the ion exchange process. 2 O can also further improve the brittleness of the glass. Li for efficient ion exchange 2 The content of O may be equal to or greater than 3 mol%. In terms of acid resistance, Li 2 The content of O may be 20 mol% or less.
[0106] Na 2 O forms surface compressive stress through ion exchange and improves the melting property of the glass. Na ions near the glass surface can be exchanged by K ions or the like through the ion exchange process. Although Na 2 O, but in order to effectively achieve the above functions, it is expected that Na 2 The content of O is equal to or greater than 1 mol%. If there is only a Li ion and Na ion exchange process without a K ion exchange process, it is expected that Na 2 The O content is equal to or less than 8 mol% in order to promote the exchange of Li and Na ions. If the K ion exchange process is carried out together, a large amount of Na 2 O. However, even in this case, it is desirable to make the content of K ions equal to or less than 20 mol % in terms of acid resistance.
[0107] K 2 O improves ion exchange properties and is associated with fragility. Although K can be eliminated or omitted 2 O, but may contain 0.5 mol% or more of K 2 O to improve ion exchange performance. In order to avoid too low fragility, K 2 The content of O may be equal to or less than 10 mol %.
[0108] MgO increases the surface compressive stress of chemically strengthened glass and improves its brittleness. When the content of MgO is equal to or greater than 3 mol%, the above functions can be effectively performed. In order to suppress or reduce devitrification that may occur when the glass is melted, it may be advantageous or beneficial to make the content of MgO equal to or less than 20 mol%.
[0109] CaO improves the meltability and fragility of the glass. CaO can be eliminated or omitted, and in order to effectively perform the above functions, it is desirable to make the CaO content equal to or greater than 0.5 mol%. If the CaO content is too large, the ion exchange performance may deteriorate. Therefore, it is desirable to make the CaO content equal to or less than 20 mol%.
[0110] Like CaO, SrO improves the meltability and fragility of glass. SrO can be eliminated or omitted, and in order to effectively perform the above functions, it is desirable to make the content of SrO equal to or greater than 0.5 mol%. If the SrO content is too large, the ion exchange performance may deteriorate. Therefore, it is desirable to make the SrO content equal to or less than 20 mol%.
[0111] BaO improves the melting and fragility of the glass. BaO can be eliminated or omitted, and in order to effectively perform the above functions, it is desirable to make the BaO content equal to or greater than 0.5 mol%. In order to avoid too low ion exchange performance, it may be advantageous or beneficial to make the BaO content equal to or less than 15 mol%.
[0112] ZnO improves the melting property of the glass. ZnO can be eliminated or omitted, and when the content of ZnO is equal to or greater than 0.25 mol%, the melting property can be significantly improved. In order to prevent or reduce the degradation of weather resistance, it is desirable to make the ZnO content equal to or less than 10 mol%.
[0113] TiO 2 Improve the brittleness of chemically strengthened glass. TiO can be eliminated or omitted 2 , and when TiO 2 When the content of TiO is equal to or greater than 0.1 mol%, the brittleness can be significantly improved. In order to prevent or reduce devitrification during melting, it is desirable to make TiO 2 The content is equal to or less than 1 mol%.
[0114] ZrO 2 The surface compressive stress can be increased and the fragility of the glass can be improved by ion exchange. ZrO can be eliminated or omitted. 2 , and when ZrO 2 When the content of ZrO is equal to or greater than 0.5 mol%, the above functions can be effectively performed. In order to suppress or reduce devitrification during melting, ZrO 2 A content of 8 mol % or less may be advantageous or beneficial.
[0115] In addition to the above-listed components, the glass composition may also include, as required, 2 O 3 ,La 2 O 3 , Nb 2 O 5 、 2 O 5 and / or Gd 2 O 3The composition of the glass article 100 can be changed by a molding process, an ion exchange process, etc., which will be further described below. In addition, the components and contents of the above-mentioned glass composition are only examples, and the glass can be formed or modified by applying the contents of various suitable components commonly used in the art.
[0116] The glass composition can be molded into a flat glass shape by various suitable methods commonly used in the art, for example, by a float process, a fusion drawing process, a trough drawing process, etc.
[0117] Subsequently, the glass molded into a flat plate shape can be cleaned by a first cleaning S20. The first cleaning S20 may be a cleaning process for removing residual particles from a previous process or processes. The cleaning process may be one of the commonly used processes. As an implementation, the cleaning process can be performed by spraying a washing liquid to clean the glass and / or immersing the glass in the washing liquid. The washing liquid is not particularly limited herein as long as it can clean the glass surface. According to one or more embodiments, deionized water (DI water) or an alkaline washing liquid containing potassium hydroxide (KOH) or sodium hydroxide (NaOH) may be used as a washing liquid. The cleaning process can be performed in warm water at room temperature or below 40°C.
[0118] Subsequently, after the first cleaning S20, stacking S30 may be performed to stack a plurality of glasses. Stacking S30 is performed by building a glass stack to easily perform subsequent cutting S40 because the glasses are easily broken if cut one by one. Stacking S30 may include a process of bonding the glasses.
[0119] In some embodiments, an adhesive may be applied to one or both surfaces of the glass to prevent or reduce the occurrence of surface scratches during processing and to form a glass stack. For example, a glass stack may be constructed by applying an adhesive to one surface of the glass, stacking another glass on the glass to which the adhesive has been applied, applying an adhesive to the glass again, stacking another glass thereon, and so on.
[0120] The method of applying adhesive is not particularly limited in this article. For example, a rubber roller with a setting or a certain softness can be used on the surface to apply adhesive. Adhesive is not particularly limited in this article. For example, UV adhesive or natural adhesive (such as rosin) can be used as adhesive.
[0121] Subsequently, the glass stack may be cut by cutting S40. In cutting S40, the final glass product may be formed into a size suitable for a device that uses the glass product. The glass stack may be processed into a unit of a large-area substrate as a mother substrate, and the mother substrate may be cut into a plurality of units. For example, if the final glass product has a size of approximately 6 inches, a glass stack having a size (e.g., 120 inches) several to several hundred times the size of the glass product may be formed. Then, by cutting, twenty flat-plate-shaped glass stacks may be obtained at a time. In this way, process efficiency can be improved compared to forming a single glass product separately.
[0122] There is no particular limitation on the cutting S40 herein as long as the glass stack can be cut into units. For example, the cutting S40 may be performed using a diamond cutting wheel, a laser, a cutting knife, or the like.
[0123] Subsequently, the glass stack may be chamfered S50 after cutting S40. Chamfering S50 may process the edge of each glass stack. For example, cutting S40 may be a step of forming a cross-sectional shape of the glass stack cut into a substantially C shape.
[0124] The chamfer S50 may be performed by a chemical polishing process. For example, the chemical polishing process may be performed by dipping and / or spraying. The polishing liquid may include a material selected from hydrofluoric acid (HF), ammonium fluoride (NH 4 F), ammonium bifluoride (NH 4 HF 2 ), sodium fluoride (NaF), sodium bifluoride (NaHF 2 ), lithium fluoride (LiF), potassium fluoride (KF) and calcium fluoride (CaF 2 ) is one or more of the clusters.
[0125] In some embodiments, before chamfering S50, physical polishing may be additionally performed to remove chipping of the cross section of the glass stack. The glass stack after chamfering S50 can prevent or reduce chipping due to edge cracking and / or recessing.
[0126] Subsequently, the glass stack may be separated S60. The separation S60 may include removing the adhesive applied to the glass stack to separate the glass from the stack individually. The separation S60 may be performed by soaking the glass stack in a stripping solution containing a swelling agent and a surfactant for the adhesive.
[0127] Subsequently, the separated glass may be cleaned through the second cleaning S70. According to an embodiment of the present disclosure, the second cleaning S70 may be performed differently from the above-described first cleaning S20.
[0128] In some embodiments, the second cleaning S70 may be a cleaning process that removes residual particles and etchants from a previous process and also improves the impact resistance of the glass. The second cleaning S70 may use deionized water (DI water). The deionized water may be used by spraying and / or dipping.
[0129] The second cleaning S70 may be performed at a temperature of 80° C. to 100° C. By performing the second cleaning S70 within the above temperature range, hydrogen ions in the deionized water may diffuse into the glass, and alkali ions in the glass may diffuse into the deionized water, so that they may replace each other. The second cleaning S70 may be performed for several minutes to several tens of minutes.
[0130] According to the implementation mode, Figure 8 and Fig. 9 As shown in FIG. 5 , the second cleaning S70 may be performed by immersing the glass 10 in a bath BA containing deionized water SO. When doing so, the temperature may range from 80° C. to 100° C. When the glass 10 is immersed in the deionized water SO, the hydrogen ions (H + ) moves into the glass by mutual diffusion at a depth of several tens of nanometers (nm) from the surface, and alkali ions (such as lithium ions (Li + ), sodium ion (Na + ) and potassium ions (K + )) moves to the deionized water SO so that they replace each other. In some embodiments, the higher the temperature of the deionized water SO, the more likely the hydrogen ions are to penetrate the glass. In some embodiments, at a temperature of 95° C. or higher, the hydrogen ions are better able to penetrate into the glass 10 to improve impact resistance.
[0131] Subsequently, a first repair S80 may be performed on the glass. The first repair S80 can remove defects in the glass and can improve the strength reduction of the side surface of the cut glass. The first repair S80 may be performed by a chemical polishing process. The chemical polishing process may be performed, for example, by dipping and / or spraying. The polishing liquid may include a selected from hydrofluoric acid (HF), ammonium fluoride (NH 4 F), ammonium bifluoride (NH 4 HF 2 ), sodium fluoride (NaF), sodium bifluoride (NaHF 2 ), lithium fluoride (LiF), potassium fluoride (KF) and calcium fluoride (CaF 2 ) is one or more of the clusters.
[0132] In some implementations, polishing of the cut glass may be further performed after the first repairing S80.
[0133] Subsequently, the third cleaning S90 may be performed on the glass. The third cleaning S90 may be a cleaning process that removes remaining particles and polishing liquid from the glass in the first repair S80 and also improves the impact resistance of the glass. The third cleaning S90 may be performed by the same process as the second cleaning S70. For example, the third cleaning S90 may be performed using deionized water (DI water) at a temperature of 80° C. to 100° C. In the third cleaning S90, hydrogen ions in the deionized water diffuse into the glass, and alkali ions in the glass diffuse into the deionized water, so that they replace each other, thereby improving the impact resistance of the glass.
[0134] Subsequently, strengthening S100 may be performed on the glass. Strengthening S100 may be performed by chemical strengthening and / or thermal tempering. For ultra-thin glass, chemical strengthening may be appropriate in order to precisely control stress distribution. In the following embodiments, chemical strengthening is applied as glass strengthening S100.
[0135] Chemical strengthening can be performed by an ion exchange process. An ion exchange process is a process in which ions within the glass are exchanged for other ions. The ion exchange process allows ions on or near the surface of the glass to be replaced or exchanged with larger ions of the same valence or oxidation state. For example, when the glass contains ions such as Li + 、Na + , K + and Rb + When the monovalent alkali metal is present, the monovalent cations on the surface can interact with Na + , K + , Rb + and Cs + Ion exchange. Fig.10 The ion exchange process is described in more detail.
[0136] Reference Fig.10 When the glass 10 containing sodium ions is immersed in a solution containing potassium nitrate (KNO 3 ) to expose the glass to potassium ions, the sodium ions in the glass are discharged to the outside, and the potassium ions can replace them. The exchanged potassium ions generate compressive stress because they have a larger ionic radius than sodium ions. The more potassium ions are exchanged, the greater the compressive stress becomes. Since the ion exchange occurs through the surface of the glass, the amount of potassium ions on the surface of the glass can be maximum. Some of the exchanged potassium ions can diffuse into the glass to increase the depth of the compression zone, for example, the depth of compression, but the amount can decrease as it moves away from the surface. Therefore, the glass can have a stress distribution with maximum compressive stress on the surface and decreasing toward the inside of the glass. However, embodiments are not limited to the above examples. The stress distribution can change according to temperature, time, and the number of ion exchange processes, whether heat treatment is performed, etc.
[0137] The ion exchange process may be performed two or more times. For example, the ion exchange process may include a primary ion exchange process and a secondary ion exchange process. The primary ion exchange process and the secondary ion exchange process may be performed in different water baths. The ion exchange process may be performed on multiple glasses simultaneously (e.g., synchronously). In some embodiments, multiple glasses may be immersed in a single bath, and ion exchange may be performed simultaneously (e.g., synchronously) in glass 10.
[0138] Subsequently, the fourth cleaning S110 may be performed. The fourth cleaning S110 may be a cleaning process that removes residual particles and molten salts from the glass in the strengthening S100 and also improves the impact resistance of the glass. The fourth cleaning S110 may be the same process as the second cleaning S70 and the third cleaning S90 described above. For example, the fourth cleaning S110 may be performed using deionized water (DI water) at a temperature of 80° C. to 100° C. In the fourth cleaning S110, hydrogen ions in the deionized water diffuse into the glass, and alkali ions in the glass diffuse into the deionized water, so that they replace each other, thereby improving the impact resistance of the glass.
[0139] Subsequently, a second repair S120 may be performed. Defects in the glass can be removed in the second repair S120. The second repair S120 may be performed by a chemical polishing process. The chemical polishing process may be performed, for example, by dipping and / or spraying. The polishing liquid may include a liquid selected from hydrofluoric acid (HF), ammonium fluoride (NH 4 F), ammonium bifluoride (NH 4 HF 2 ), sodium fluoride (NaF), sodium bifluoride (NaHF 2 ), lithium fluoride (LiF), potassium fluoride (KF) and calcium fluoride (CaF 2 ) is one or more of the clusters.
[0140] Finally, the fifth cleaning S130 may be performed. The fifth cleaning S130 may be a cleaning process that removes remaining particles and etchants from the glass in the second repair S120 and also improves the impact resistance of the glass. The fifth cleaning S130 may be the same process as the second cleaning S70, the third cleaning S90, and the fourth cleaning S110 described above. For example, the fifth cleaning S130 may be performed using deionized water (DI water) at a temperature of 80° C. to 100° C. In the fifth cleaning S130, hydrogen ions in the deionized water diffuse into the glass, and alkali ions in the glass diffuse into the deionized water, so that they replace each other, thereby improving the impact resistance of the glass.
[0141] The glass article thus produced can have an increased hydrogen ion strength (e.g., concentration) and a reduced alkali ion strength (e.g., concentration) at a depth of tens of nanometers from the surface. In some embodiments, the ratio of the strength (e.g., concentration) of hydrogen ions at a depth of 30 nm from the surface of the glass article to the strength (e.g., concentration) of ion-exchanged hydrogen ions at the surface of the glass article may be 1:4 to 1:6. According to an embodiment of the present disclosure, the ratio of the strength (e.g., concentration) of hydrogen ions at a depth of 30 nm from the surface of the glass article to the strength (e.g., concentration) of ion-exchanged hydrogen ions at the surface of the glass article may be equal to or greater than 1:5.
[0142] In some embodiments, the ratio of the alkali ion strength (e.g., concentration) at a depth of 30 nm from the surface of the glass article to the strength (e.g., concentration) of the alkali ions exchanged at the surface of the glass article may be equal to or greater than 1:0.1. According to embodiments of the present disclosure, the ratio of the alkali ion strength (e.g., concentration) at a depth of 30 nm from the surface of the glass article to the strength (e.g., concentration) of the alkali ions exchanged at the surface of the glass article may be in the range of 1:0.05 to 1:0.1.
[0143] The ratio is obtained by measuring the number, e.g., intensity (e.g., concentration) of hydrogen ions and alkali ions at a depth of several tens of nanometers from the surface of the glass article by D-SIMS (dynamic secondary mass spectrometry). In the glass article according to the embodiment of the present disclosure, the ratio of the intensity (e.g., concentration) of hydrogen ions at a depth of 30 nm from the surface of the glass article relative to the intensity (e.g., concentration) of hydrogen ions at the surface may be 1:4 to 1:6, and the ratio of the intensity (e.g., concentration) of alkali ions may be 1:0.05 to 1:0.1. At a depth of 30 nm from the surface of the glass article, the ratio of the intensity (e.g., concentration) of ion-exchanged hydrogen ions and alkali ions at the surface of the glass article no longer increases, and thus becomes saturated.
[0144] As shown in the experimental examples described below, by applying the above cleaning process, as the strength (e.g., concentration) of hydrogen ions at the surface of the glass article increases, the strength (e.g., concentration) of alkali ions can be reduced. Therefore, the impact resistance of the surface of the glass article can be improved.
[0145] Hereinafter, the embodiments will be described in more detail with reference to examples and experimental examples.
[0146] Preparation example
[0147] A glass plate having a thickness of 100 μm was prepared, and then subjected to first cleaning, stacking, cutting, chamfering, separation, second cleaning, first repairing, third cleaning, strengthening, fourth cleaning, second repairing, and fifth cleaning to produce a glass product.
[0148] Comparative Example
[0149] The glass was immersed in deionized water (DI water) and potassium hydroxide (KOH) at a temperature of 40° C. for 20 minutes, and first to fifth cleanings were performed to produce a glass product.
[0150] Example 1
[0151] A glass article was produced under the same conditions as those in Comparative Example, except that the glass was immersed in deionized water (DI water) at a temperature of 80° C. for 20 minutes, and the first to fifth cleanings were performed.
[0152] Example 2
[0153] A glass article was produced under the same conditions as those in Comparative Example, except that the glass was immersed in deionized water (DI water) at a temperature of 80° C. for 40 minutes, and the first to fifth cleanings were performed.
[0154] Example 3
[0155] A glass article was produced under the same conditions as those in Comparative Example, except that the glass was immersed in deionized water (DI water) at a temperature of 100° C. for 40 minutes, and the first cleaning to the fifth cleaning were performed.
[0156] Experimental Example: Pen Test
[0157] The glass articles of Comparative Example, Example 1, Example 2, and Example 3 were attached to the OLED panel as cover windows, and then the pen pressure test and the pen drop test were performed. Fig.11 and Fig.12 as shown in .
[0158] Fig.11 is a graph showing the results of a pen pressure test of glasses according to Examples and Comparative Examples. Fig.12 is a graph showing the results of a pen drop test on glasses according to Examples and Comparative Examples.
[0159] Reference Fig.11 In the pen pressure test, a panel with a glass product attached thereto is fixed on a stone table, and a pen is fixed to a universal testing machine (UTM). The diameter of the pen is 0.3π, and the weight is 5.35 g. The pen is dropped at a speed of 6 mm / min to press the glass product. The pen is dropped repeatedly, and the breaking load is checked when the glass breaks.
[0160] The breaking load of the glass article according to the comparative example was 1.03 kgf (kilogram force). On the other hand, the breaking load of the glass article according to Example 1 was 1.17 kgf, the breaking load of the glass article according to Example 2 was 1.21 kgf, and the breaking load of the glass article according to Example 3 was 1.32 kgf.
[0161] It can be seen from the results that the breaking load at the break of the glass article increases with the temperature range from the second cleaning process to the fifth cleaning process and with the increase of the immersion time.
[0162] Reference Fig.12 , in the pen drop test, a panel with a glass product attached thereto is fixed on a stone table. Then, a pen is fixed to a machine using an electromagnet, and then the pen is dropped onto the glass product by operating a switch. The pen has a diameter of 0.3π and a weight of 5.35g, and the drop height of the pen moves 0.1cm within a range of 0.5cm to 30cm. The pen is dropped repeatedly until the glass breaks, and the height is checked.
[0163] When the pen was dropped at a height of 20.38 cm, the glass product according to the comparative example was broken. On the other hand, when the pen was dropped at a height of 21.88 cm, the glass product according to Example 1 was broken, when the pen was dropped at a height of 22.38 cm, the glass product according to Example 2 was broken, and when the pen was dropped at a height of 24.22 cm, the glass product according to Example 3 was broken.
[0164] It can be seen from the results that the drop height of the pen increases with the temperature range of the second cleaning process to the fifth cleaning process and with the increase of the soaking time.
[0165] As can be seen from the experimental examples, the glass product produced according to the method for producing a glass product of the present disclosure has improved impact resistance.
[0166] Experimental example: Hydrogen ion and alkali ion analysis
[0167] The intensity of hydrogen ions and the intensity of alkali ions at a depth of 30 nm from the surface of the glass articles produced according to the above Comparative Example and Example 3 were measured using D-SIMS (Dynamic Secondary Mass Spectrometry). The results are shown in Table 1 below and Fig.13 and Fig.14 as shown in .
[0168] Fig.13 is a graph showing the distribution of hydrogen ions in glass products measured according to Examples and Comparative Examples. Fig.14 is a graph showing the distribution of alkali ions in glass products measured according to Examples and Comparative Examples.
[0169] Table 1
[0170]
[0171] Combined with the above table 1 reference Fig.13 and Fig.14 , the glass article according to the comparative example showed that the ratio of the intensity of hydrogen ions at the glass surface to the intensity at a depth of 30 nm of the glass article was 370%, and the ratio of the intensity of alkali ions was 9.8%. In contrast, the glass article according to Example 3 showed that the ratio of the intensity of hydrogen ions at the glass surface to the intensity at a depth of 30 nm of the glass article was 517.7%, and the ratio of the intensity of alkali ions was 0.1%.
[0172] It can be seen from the results that, at the glass surface of the glass article according to Example 3, hydrogen ions significantly increased, while alkali ions significantly decreased, compared with the comparative example.
[0173] At the end of the detailed description, those skilled in the art will appreciate that many changes and modifications can be made to the disclosed embodiments without departing substantially from the principles of the present disclosure. Therefore, the disclosed embodiments of the present disclosure are used only in a general and descriptive sense, and not for the purpose of limitation.
Claims
1. A glass product, wherein: A ratio of the intensity of hydrogen ions at a depth of 30 nm from a surface of the glass article to the intensity of hydrogen ions at the surface is equal to or greater than 1:
4.
2. The glass product according to claim 1, wherein: The ratio of the intensity of hydrogen ions at the depth of 30 nm from the surface to the intensity of hydrogen ions at the surface ranges from 1:4 to 1:
6.
3. The glass product according to claim 1, wherein: The ratio of the intensity of alkali ions at the depth of 30 nm from the surface to the intensity of alkali ions at the surface ranges from 1:0.05 to 1:0.
1.
4. The glass product according to claim 1, wherein: The glass article includes LAS glass ceramics.
5. The glass product according to claim 4, wherein: The glass product includes SiO2, Li2O and Al2O3, and also includes at least one selected from Na2O, K2O, MgO, P2O5, B2O3, CaO, SrO, BaO, ZnO, TiO2 and ZrO2.
6. The glass product according to claim 1, wherein: The glass article has a thickness in the range from 20 μm to 100 μm.
7. The glass product according to claim 1, wherein: The glass article is foldable.
8. A method for producing a glass product, the method comprising: Forming glass; stacking the glasses to construct a glass stack; cutting the glass stack to separate the glass stack into individual glasses; Performing a first repair on the glass; Performing a first cleaning on the glass; strengthening the glass; performing a second cleaning on the glass; performing a second repair on the glass; as well as performing a third cleaning on the glass, Herein, at least one selected from the first cleaning, the second cleaning, and the third cleaning uses deionized water at a temperature in a range of 80°C to 100°C.
9. The method for producing a glass product according to claim 8, wherein: At least one selected from the first cleaning, the second cleaning, and the third cleaning is performed by dipping and / or spraying.
10. The method for producing a glass product according to claim 8, wherein: At least one selected from the first cleaning, the second cleaning, and the third cleaning is performed for several minutes to several tens of minutes.
11. The method for producing a glass product according to claim 8, wherein: In at least one selected from the first cleaning, the second cleaning, and the third cleaning, hydrogen ions and alkali ions are ion-exchanged at the surface of the glass.
12. The method for producing a glass product according to claim 8, further comprising: performing a fourth cleaning on the glass between the separation and the first repairing, Wherein, the fourth cleaning uses deionized water at a temperature in the range of 80°C to 100°C.
13. The method for producing a glass product according to claim 8, further comprising: chamfering the glass after cutting the glass stack, Wherein, the chamfering is performed by a chemical polishing process.
14. A display device, comprising: A display panel, the display panel comprising a plurality of pixels; a cover window, wherein the cover window is located on the display panel; as well as an optically transparent coupling layer, the optically transparent coupling layer being located between the display panel and the cover window, Wherein, a ratio of the intensity of hydrogen ions at a depth of 30 nm from a surface of the cover window to the intensity of hydrogen ions at the surface is equal to or greater than 1:
4.
15. The display device according to claim 14, wherein: In the cover window, the ratio of the intensity of hydrogen ions at the depth of 30 nm from the surface to the intensity of hydrogen ions at the surface ranges from 1:4 to 1:
6.
16. The display device according to claim 14, wherein: In the cover window, a ratio of an intensity of alkali ions at a depth of 30 nm from the surface to an intensity of alkali ions at the surface ranges from 1:0.05 to 1:0.
1.
17. The display device according to claim 14, wherein: The cover window comprises LAS glass ceramic.
18. The display device according to claim 14, wherein: The cover window includes SiO2, Li2O and Al2O3, and also includes at least one selected from Na2O, K2O, MgO, P2O5, B2O3, CaO, SrO, BaO, ZnO, TiO2 and ZrO2.
19. The display device according to claim 14, wherein: The cover window has a thickness ranging from 20 μm to 100 μm.
20. The display device according to claim 14, wherein: The cover window is foldable.